Childhood adversity profiles and adult psychopathology in a representative Northern Ireland study. (October 2015) - McLafferty, Margaret; Armour, Cherie; McKenna, Aine; O'Neill, Siobhan; Murphy, Sam; Bunting, Brendan
Abstract: Childhood adversities are key aetiological factors in the onset and persistence of psychopathology. The aims of this study were to identify childhood adversity profiles, and investigate the relationship between the adversity classes and psychopathology in Northern Ireland. The study utilized data from the Northern Ireland Study of Health and Stress, an epidemiological survey ( N  = 1986), which used the CIDI to examine mental health disorders and associated risk factors. Latent Class Analysis revealed 3 distinct typologies; a low risk class (n  = 1709; 86%), a poly-adversity class ( n  = 122; 6.1%), and an economic adversity class ( n  = 155; 7.8%). Logistic Regression models revealed that individuals in the economic adversity class had a heightened risk of anxiety and substance disorders, with individuals in the poly-adversity class more likely to have a range of mental health problems and suicidality. The findings indicate the importance of considering the impact of co-occurring childhood adversities when planning treatment, prevention, and intervention programmes.